A time bomb for the Euro? Understanding Germany's current account surplus - Jan Priewe (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2018)
The paper analyses the rise of the current account balance in Germany by around ten percentage points (relative to GDP) in the period 1999-2016. A big part of the rise is due to subdued domestic final demand which tends to suppress growth of imports. This demand-side effect has to do with weak wage dynamics, unequal income distribution and fiscal restraint. Despite ups and downs, the trend seems to be persistent. On the supply side, the cost and price competitiveness of the German economy is superior in European comparison. However, much more important is the superior non-price competitiveness in various dimensions. Exports grow in line with world exports which tend to grow markedly faster than imports and GDP in Germany. If this wedge between growth rates of imports and exports continues, the current account tends to rise, irrespective of short-term ups and downs. Germany follows an unsustainable trend.On the supply side, it is the strength of German manufacturing, the basis of the country's surplus. It has emerged in parallel with a process of creeping deindustrialisation in other EMU member states. The export championship, seemingly the crown jewel of the economy, has the mirror image of an Achilles heel. The surplus cannot be understood without the dysfunctions of the EMU which has no mechanisms to prevent and correct current account imbalances. Many policy makers are blinded by export success and vested interests of German export industries. They trust in "laisser-faire" and "no activism" advice, in contrast to concerns from the European Commission and the IMF. In this sense, there exists a time-bomb for the cohesion of the Euro area. – – In der Studie wird der Anstieg des deutschen Leistungsbilanzsaldos um zehn Prozentpunkte (relativ zum BIP) im Zeitraum 1999-2016 untersucht. Ein erheblicher Teil des Anstiegs ist dem schwachen Wachstum der Endnachfrage geschuldet, das Importe gebremst hat. Diese Nachfrageeffekte rühren aus der schwachen Lohndynamik, der veränderten Einkommensverteilung und einer zu restriktiven Fiskalpolitik. Trotz der Aufs und Abs der verschiedenen Impulse ist der Trend zum Anstieg des Leistungsbilanzüberschusses stabil. Auf der Angebotsseite hat die deutsche Volkswirtschaft eine - im europäischen Vergleich - überlegene preisliche Wettbewerbsfähigkeit. Wichtiger ist jedoch die nicht-preisliche Wettbewerbsfähigkeit in verschiedenen Dimensionen. Die Exporte wachsen ähnlich stark wie die Weltexporte, während die Importe und das deutsche BIP viel langsamer wachsen. Der Keil zwischen der Wachstumsrate der Exporte und der der Importe lässt den Überschuss tendenziell weiter steigen, unabhängig von kurzfristigen Einflüssen. Deutschland folgt offensichtlich einem nicht-nachhaltigem Trend.Auf der Angebotsseite ist die Stärke der verarbeitenden Industrie die Basis der Exportüberschüsse. Diese Stärke hat sich parallel zur schleichenden Deindustrialisierung in den meisten anderen EU-Ländern herausgebildet. Erscheinen die starken Exporte wie ein Kronjuwel der deutschen Volkswirtschaft, so sind sie doch ihre Achillesferse. Diese kann nicht verstanden werden ohne die europäische Währungsunion, die keine Mechanismen entwickelt hat, relative außenwirtschaftliche Ungleichgewichte zu korrigieren.Viele Politiker haben sich durch die Exporterfolge und auch die Interessenlage der Exportindustrien blenden lassen. Sie vertrauen auf Ratschläge für "laisser faire" und "kein Aktivismus", im Gegensatz zu deutlichen Mahnrufen der Europäischen Kommission und des IWF. In diesem Sinne sind die Exportüberschüsse eine Zeitbombe, die die Kohäsion in der Währungsunion untergräbt.
urn:nbn:de:101:1-201804052841
Keywords: 330